Implementing Jambi Culture-Based Interactive E-Book with Toontastic 3D Animation Using RME to Improve Learning Interest - Mujahidawati Mujahidawati; Asih Nur Ismiatun; Syaiful Syaiful; Novferma Novferma; Febbry Romundza (Universitas Lambung Mangkurat, 2026)
This study aims to examine the effectiveness of implementing a Jambi culture-based interactive e-book integrated with FILATOD, a Toontastic 3D animation-based learning medium, using the Realistic Mathematics Education (RME) approach to improve students’ learning interest in mathematics. This study employed a quasi-experimental design with a pretest–posttest control group involving 64 students of SMPN 7 Muaro Jambi. Data were collected using a learning interest questionnaire and classroom observation sheets. The results showed that the experimental group experienced a significant increase in learning interest, with the mean score improving from 66.31 in the pretest to 84.47 in the posttest, while the control group increased from 65.84 to 72.06. Independent-samples t-test analysis indicated a significant difference between the two groups (p < 0.05), with a very large effect size (d = 1.28). These findings demonstrate that integrating Jambi cultural contexts, Toontastic 3D animation, and RME specifically improves students’ learning interest by connecting mathematical concepts to familiar local experiences, presenting contextual problems through engaging animated narratives, and guiding students to construct mathematical understanding from realistic situations. The combination of these three elements strengthens students’ attention, curiosity, enjoyment, participation, and persistence during mathematics learning. Therefore, culturally contextualized digital learning media supported by animation and RME can serve as an innovative instructional strategy to enhance students’ affective engagement and improve the quality of mathematics learning.